PERANCANGAN APLIKASI PSIKOTES BERBASIS WEBSITE PADA LAYANAN PSIKOLOGI PENJURUSAN DAN KARIR - Perani Rosyani; Achmad Anshori Cahyaabdillah; Almaghribi Risandi; Rizki Maulana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Psychotest is a test conducted to measure individual aspects psychologically. This test can be in the form of a written, projective, or verbal evaluation. Psychological tests are also part of a series for students to choose a major to the next level, which generally has an important meaning. To face the next level, students must prepare themselves by looking for references about the majors they are interested in and the job prospects they will face in the future. With this web-based psychotest simulation application, it is hoped that it can help students or students in providing an overview in choosing college majors and also help determine the identity of these students in the ability and willingness of these students to continue their education in higher education.